Moving beyond a simple model of luminescence rings in quantum well structures - Snoke, D; Denev, S; Liu, Y; Simon, S; Rapaport, R; Chen, G; Pfeiffer, L; West, K (2004)
The dramatic appearance of luminescence rings with radius of several hundred microns in quantum well structures can be understood through a fairly simple nonlinear model of the diffusion and recombination of electrons and holes in a driven nonequilibrium system. The ring corresponds to the boundary between a positive hole gas and a negative electron gas in steady state. While this basic effect is now well understood, we discuss several other experimental results which cannot be explained by this simple model.